The Use of Glutaraldehyde Tanning Materials for Goat Skin Tanning - Laili Rachmawati; Emiliana Anggriyani (Faculty of Animal Science, Universitas Gadjah Mada, 2018)
Tanning process using free chromed material is needed to reduce toxic content in leather. The aims of this study is to increase byproducts of livestock by goat skin tanning with free chrome tanning materials. This study used glutaraldehyde as tanning materials. Goat skins were tanned become upholstery leather, and then physical quality was determined. The materials of this study were pickle goat skin. Physical testing conducted in Balai Besar Kulit, Karet dan Plastik (BBKKP) Yogyakarta. The results were analyzed descriptively using SPSS version 17.0 for Windows. Statistical analysis showed that the value of tensile strength, elongation, tear strength, sewing strength, scrub resistance of paint to dry and wet were 166.025 ± 72.315 kg/cm²; 69.910 ± 9.107%; 26.785 ± 6.031 N/cm; 115.120 ± 18.681 kg/cm; 0.775 ± 0.353; 0.775 ± 0.353 respectively. This study showed that the physical quality of upholstery leather which tanned using free chrome tanning materials have the physical qualities that met with SNI standard for leather upholstery.